Occupational Injuries and Illnesses and Associated Costs in Thailand - Phayong Thepaksorn; Sathirakorn Pongpanich (Elsevier, 2014)
Background: The purpose of this study was to enumerate the annual morbidity and mortality incidence and estimate the direct and indirect costs associated with occupational injuries and illnesses in Bangkok in 2008. In this study, data on workmen compensation claims and costs from the Thai Workmen Compensation Fund, Social Security Office of Ministry of Labor, were aggregated and analyzed. Methods: To assess costs, this study focuses on direct costs associated with the payment of workmen compensation claims for medical care and health services. Results: A total of 52,074 nonfatal cases of occupational injury were reported, with an overall incidence rate of 16.9 per 1,000. The incidence rate for male workers was four times higher than that for female workers. Out of a total direct cost of $13.87 million, $9.88 million were for medical services and related expenses and $3.98 million for compensable reimbursement. The estimated amount of noncompensated lost earnings was an additional $2.66 million. Conclusion: Occupational injuries and illnesses contributed to the total cost; it has been estimated that workers' compensation covers less than one-half to one-tenth of this cost.